Skill Sets for Family Members and Friends to Help Motivate a Smoker to Seek Treatment: Research to Practice - Brockman, Tabetha A. (Addict Res Theory, 2018)
Translation of effective behavioral interventions is a key challenge for the addictions treatment field. With the goal of disseminating an effective behavioral intervention to practice, this narrative study describes tobacco cessation coaches’ skills sets and provides an illustrative case study of a 1-session phone intervention between a coach and a concerned family member who wants to help their smoker quit. Delivered through a quitline by quitline coaches, the intervention consisted of a 15–30 minute phone session and written materials. The goal of the intervention was for family members and friends (support persons) to encourage their smoker to use a quitline. Data were collected from transcripts of 193 audiotapes of the one session phone intervention from a previous trial (Patten et al., In Print). Using content analysis, major themes regarding barriers and challenges within the sessions and coaches’ solutions assisted in selecting case study illustrating the dialogue between a coach and a support person, as well as demonstrating the coaches’ skill sets used to deliver the session. In addition, the barriers and challenges among support persons (i.e., uncertainty about how to approach the smoke, the smoker is not ready to quit) and the coaches’ responses and suggestions are illustrated. These types of data could be useful to clinicians, providers and others interested in implementing a behavioral intervention for nonsmokers who want to support a smoker to quit.